Social cues in the expression of sequential alternative reproductive tactics in young males of the peacock blenny, Salaria pavo - Fagundes, Teresa (2013)
Phenotypic change in response to variation in environmental cues has been widely documented in fish. Transitions in social dominance, in particular, have been shown to induce a rapid switch in reproductive phenotypes in many species. However, this effect has been mainly studied in adults and focused on behavioural transitions. The way social cues constraint the phenotypic development of juveniles remains poorly studied in fish. We tested the importance of social dominance and density in the phenotypic development of juveniles of the peacock blenny Salaria pavo. This species shows sequential male alternative reproductive tactics. In the first breeding season males can reproduce as nest-holders or as parasitic males (female-mimicking), or postpone reproduction; from the following season afterwards all males reproduce as nest-holders. Parasitic males have relatively larger testes that lack a testicular gland, present in the testes of nest-holders. The testicular gland is the main source of androgens in the testes and accordingly nest-holders have higher circulating androgen levels. In addition, exogenous androgen administration to parasitic males promotes the development of secondary sexual characters (SSC) only present in nest-holders such as a head crest and an anal gland. We raised juveniles under a high or low-density treatment and monitored social interactions for 1 month. No significant effect of density on the development of juvenile males was detected. However, within each replicate, the relative body size of juvenile males at the beginning of the experiment determined their dominance status, with dominant males developing towards the nest-holder morphotype. Dominant males engaged in more nest defence behaviour, showed larger testicular glands, had higher levels of 11-ketotestosterone (11-KT) and testosterone (T) and developed more SSC, as compared to subordinate males. However, these effects of social dominance were moderated by body condition as only dominant males in good body condition developed SSC. The effect of social dominance and of the area of the testicular gland on the development of SSC was mediated by 11-KT and on the expression of nest defence behaviour by T. Interestingly, in spite of the higher androgen levels and more pronounced morphologic development of SSC in dominant individuals, gonadal development was independent of social dominance and most fish still had underdeveloped testis at the end of the experiment. In conclusion, social dominance promoted the development of the testicular gland, an increase in circulating androgen levels and the development of SSC, but did not promote testicular development. This suggests a dissociation of mechanisms underlying sexual maturation and the expression of male reproductive traits. This dissociation seems to be the key for the occurrence of female-mimicking males in this species, which are sexually mature despite lacking the SSC typical of nest-holders.